Inclusion of Different Level of Khesari for Promotion in Broiler - Azad, Md. H.; Tiwari, M. R.; Poudel, N. R.; Shah, B. M.; J.C, B. K.; Chaudhary, G. P. (Nepalese Veterinary Journal, 2019)
An experiment was conducted at Regional Agricultural Research Station, Parwanipur, Bara for 38 days to test the effect of Khesari leaves inclusion in broiler feed and its effect on growth performance. Altogether 135 day-olds Cobb-500 broiler birds were procured from Shivam Hatchery, Birgung and divided into 3 treatments with 3 replications (15 birds in each replication) by using completely randomized design. Concentrate feed was purchased from Posak Feed industry, Birgung. Control group (T1) was fed without inclusion of Khesari leaves and whereas T2 and T3 groups were fed 5% and 10 % Khesari leaves added feed respectively. Diet replaced with 5 % and 10 % Khesari leaves were offered from 14th day of trial to T2 and T3 broilers group respectively. Experimental birds were provided adlib amount of grower feed (B1) for 21 days and that after finisher feed (B3) for 21 days and had easily access to drinking water. Feed intake was recorded daily and body weight gain was measured in 7 days interval. Experiment revealed that highest weight gain was observed in T3 (2.55 kg) followed by T1 (2.48) where inclusion of 10 % Khesari leaves and normal feed respectively, which was also significant among diet groups. Similarly, highest cumulative feed intake was also observed for T3 (4.23 kg) followed by T1 (3.90 kg) which was also significant among diet groups. Experiment suggested that further study should be carried out to precise the appropriate level of organic acids inclusion and higher cost benefit ratio.